Efforts to Prevent Radicalism for Children in School/Madrasah - Hardiansyah; Sriyanti (Journal of Contemporary Gender and Child Studies, 2025)
This study discusses efforts to prevent radicalism in Elementary Schools (SD MI). The purpose of the study is to analyze effective strategies in overcoming the potential for radicalism in elementary education environments. This study uses qualitative methods, namely by collecting library data, reading, and taking notes on the discussion material. This study discusses the steps that have been taken by SD/MI in preventing and overcoming radicalism. The results of this study provide insight into the successes and challenges in implementing efforts to prevent radicalism among children, viewing it as an integral part of forming a safe and peaceful society. As well as the importance of a holistic approach involving schools, families, and communities in creating an environment that supports the values of tolerance, pluralism, and intercultural understanding. It is important for children and educators to face and overcome understandings of radicalism. The implications of these findings can provide a foundation for developing more effective radicalism prevention strategies among elementary school children.